2022
DOI: 10.1111/jfpp.16716
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of kinnow (citrus reticulate) peel and its effect on the quality of muffin

Abstract: Kinnow peel powder (KPP) characterization (particle size; <180 μm, 180–250 μm, and 250–500 μm) showed that the particle size under 180 μm posses higher bulk density, color value L* & b*, oil absorption capacity, water solubility, and lower water holding capacity. Total phenolic content, total flavonoid content, and antioxidant properties of KPP varied in the range of 10.1 ± 0.21 to 10.9 ± 0.03 mg GAE/g, 4.96 ± 0.59 to 6.09 ± 0.56 mg QE/g, and 77.5 ± 0.96 to 87.2% ± 0.51%, respectively. An increase in particle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 59 publications
2
4
0
Order By: Relevance
“…As reported by Olawuyi and Lee [16], the addition of mushroom and carrot powders to muffin formulations increased their weights due to fibre addition. Another study about refined wheat flour mixed with kinnow peel powder suggested that higher fibre content results in less moisture loss during baking, thus increasing muffin weight [23]. Contrarily, and in line with the results of the present paper, other researchers have reported a volume decrease when incorporating pomace powder into cakes [17] and muffins [16] and have attributed this result to the increased fibre content, which worsens the viscoelastic behavior of doughs.…”
Section: Muffin Dough and Product Characterizationsupporting
confidence: 89%
See 2 more Smart Citations
“…As reported by Olawuyi and Lee [16], the addition of mushroom and carrot powders to muffin formulations increased their weights due to fibre addition. Another study about refined wheat flour mixed with kinnow peel powder suggested that higher fibre content results in less moisture loss during baking, thus increasing muffin weight [23]. Contrarily, and in line with the results of the present paper, other researchers have reported a volume decrease when incorporating pomace powder into cakes [17] and muffins [16] and have attributed this result to the increased fibre content, which worsens the viscoelastic behavior of doughs.…”
Section: Muffin Dough and Product Characterizationsupporting
confidence: 89%
“…Fortification of bakery products with plant-based functional ingredients has gained interest in recent years [20]. Low-cost fruit and vegetable waste has been proposed to replace wheat flour for the production of cake, bread, muffins, or breadsticks using potato, mango, kinnow, pomegranate, and grape pomace or peel powder [21][22][23][24][25] or [14]. However, less research has been conducted on gluten-free flours [26].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finer particles show lower peak temperatures while coarse particles show higher peak temperatures. It could be due to the fact that coarse particles require higher temperatures to maintain their rubbery state of transition (Khaleel et al, 2022).…”
Section: Thermal Properties Of Raw Materialsmentioning
confidence: 99%
“…( 10) [30]. The particle size distribution (PSD) of the black pepper powder was observed in the form of D 10 , D 50 , D 60 , and D 90 , which indicate the total percentiles of particle sizes below the values of 10%, 50%, 60%, and 90%, respectively, in a cumulative size distribution [35][36][37], and coefficient of uniformity (CU) and span which indicate the width of distribution [38] were calculated using eqs. ( 11) and ( 12), respectively.…”
Section: Particle Size Distribution (Psd)mentioning
confidence: 99%